Options and Challenges for a New Electricity Market Design in the Crisis - Axel Ockenfels (Wirtschaftsdienst)
Abstract Policymakers seem determined to intervene in the design of the wholesale electricity market to redistribute crisis gains and burdens. However, some of the proposed interventions would exacerbate the problems. Options for a new electricity market design are outlined and the associated implementation challenges are discussed. The most promising market designs use tax gains from inframarginal power generation. However, these designs also face significant challenges due to widespread forward hedging in the market.